COVID - 19: Daily challenges and coping strategies in the face of social isolation (Research, Society and Development, 2020)
The Covid-19 pandemic represents one of the greatest global health challenges of this century. In the first week of April, just a few months after the outbreak in China in December 2019, more than 1.5 million have been reported cases and 85,000 deaths worldwide, and an even greater number of cases is expected and deaths will occur in the coming months. In Brazil, until April 8, 2020, 15,927 confirmed cases and 800 deaths were recorded by Covid-19. It is a narrative literature review, which aimed to describe the main effects of this social isolation, observing the factors that can contribute or hinder this process, but also to correlate possible coping strategies in the face of the need for social isolation. The final sample consisted of only 15 references, including only those most relevant to this study. After reflective reading, two categories emerged: Main effects of social isolation on the individual's daily life in the face of the covid-19 pandemic and Strategies for coping with the effects of social isolation on the individual's daily life in the face of the covid-19 pandemic. It is concluded that the effects caused by Covid-19 will extend over time, in a social, physical and psychic way. In addition, the shutdown of many services has resulted in a higher rate of unemployment and economic impact, affecting large and small companies. It was necessary to reinvent and adapt to the resources available at the moment, making it possible in some way to continue the activities and maintain the source of income and, above all, mental health.